2021
DOI: 10.1021/acs.jpca.0c11002
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Spectra of Gd2O2 and Nonmonotonic Photon-Energy-Dependent Variations in Populations of Close-Lying Neutral States

Abstract: Photoelectron spectra of Gd2O2 – obtained with photon energies ranging from 2.033 to 3.495 eV exhibit numerous close-lying neutral states with photon-energy-dependent relative intensities. Transitions to these states, which fall within the electron binding energy window of 0.9 and 1.6 eV, are attributed to one- or two-electron transitions to the ground and low-lying excited neutral states. An additional, similar manifold of electronic states is observed in an electron binding energy window of 2.1–2.8 eV, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…31 From the standpoint of orbital angular momentum, there is no explanation for the features with perpendicular PAD, unless the orbital angular momentum of the ejected electron is affected by PEVE interactions in a way that was not observed in previous studies on similar strongly correlated systems. 13 Considering the strong coupling between unpaired outervalence electrons and the 4f 7 cores evident from the energy associated with α → β spin flips in the δ orbitals (ca. 0.8 eV, Table 1), it is conceivable that there is similarly strong coupling between the orbital angular momentum of the ejected electron and the projection of the spin angular momentum of the 4f 7 cores.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 From the standpoint of orbital angular momentum, there is no explanation for the features with perpendicular PAD, unless the orbital angular momentum of the ejected electron is affected by PEVE interactions in a way that was not observed in previous studies on similar strongly correlated systems. 13 Considering the strong coupling between unpaired outervalence electrons and the 4f 7 cores evident from the energy associated with α → β spin flips in the δ orbitals (ca. 0.8 eV, Table 1), it is conceivable that there is similarly strong coupling between the orbital angular momentum of the ejected electron and the projection of the spin angular momentum of the 4f 7 cores.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9−11 We recently reported the effects of strong electron−neutral interactions in the photoelectron spectra of Sm 2 O − and Gd 2 O 2 − . 12,13 Specifically, the probability of populating excited neutral states via anion detachment increased relative to the ground-state neutral with decreasing photon energy and, therefore, decreasing photoelectron kinetic energy (e − KE); this observation is opposite of what would be expected to arise from threshold effects. 14 Pronounced effects were observed in a number of Sm-rich suboxide clusters, 15,16 but it was not observed in homometallic Ce-homologues, which implicated the greater density of electronic states from Sm's 4f 5 or 4f 6 subshell occupancy, compared to Ce's lone 4f electron.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 These features show exceptional agreement with the term energies of NdO determined from the LIF spectra of Linton and coworkers, 27 who identified the corresponding neutral states as belonging to the Ω = 4, 5 manifolds; we thus consider the final neutral states reached in transitions A-G to belong to the same Ω = 4, 5 states. Previous experiments employing photoelectron spectroscopy of lanthanide monoxides 20,[64][65][66][67] have shown that photodetachment from a metalcentered 6s orbital, as is the case for the NdO¯ anion, imposes a ∆Ω = ± ½ selection rule. Our results then strongly suggest detachment from an NdO¯ ground electronic state with Ω = 4.5, thus allowing photodetachment transitions to states with Ω = 4, 5.…”
Section: A Low-ebe Structure Of Ndomentioning
confidence: 99%